Efficacy and safety of tranexamic acid in hip fracture surgery: A comparative study of 613 patients. Issue 4 (April 2022) - AlSumadi, Mutaz; Mahmood, Aatif; Whittam, David; Kharma, Lara; Ashour, Rami; Banim, Ronan
Background: Blood loss is a major concern in the frail elderly patient undergoing hip fracture surgery. The objective of this study was to investigate the efficacy of tranexamic acid in reducing blood loss and allogenic blood transfusions. The study also investigated the safety profile by comparing rates of thromboembolic events, Methods: A total of 613 patients with hip fractures were included in the study. Patients received 1g of tranexamic acid on induction of anaesthesia. Postoperative haemoglobin was measured on day one. Blood loss was calculated, and blood transfusion was recorded. Results: Tranexamic acid use resulted in a higher mean postoperative haemoglobin (110.3 ± 15.9 vs 106.8 ± 16.2; p  = 0.023) and reduced mean estimated blood loss (571.3 ± 150.4 vs 678.3 ± 201.2; p  = 0.001). There was also a significantly reduced number of transfusions in tranexamic acid group (13% vs 28%; p  = 0.002). There was no difference in rates of deep vein thrombosis (4 vs 3; p  = 0.98) or pulmonary embolism (2 vs 2; p  = 1). Conclusion: The use of tranexamic acid is effective in reduction of blood loss and rates of blood transfusion, without an apparent increase in adverse thromboembolic events.